Plataforma móvil con realidad aumentada para la enseñanza de los cálculos (2014)
The mobile applications have generated big impact in the society; have been applied in some areas of human interest. In this project take advantage of mobile applications with augmented reality (AR) for get better academic performance of the students and achieve a meaningful learning in the calculus courses. For its were analyzed the thematic contents of the calculus differential, integral and several variables and was developed a mobile platform in that log in to detailed information of the courses topics with examples and exercises. Also, has an interface for connecting with a web service, in that can solve high percent of calculus application, such as: limits, derivate, integrals. This allows show the graphics using the AR from markers based on the formal definitions of the functions. Finally, were applied test to students without use of the platform and then use, appreciate an improvement in the academic performance and learning of the topics. According to the above conclude that the use of the mobile application with augmented reality is relevant for the teaching of calculus.